Concomitant challenge of a very large cervical fibroid with bilateral ovarian masses - Anand, Ashok R.; Gohil, Dhruv Pravin (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Occurrence of cervical fibroids is rare. Seldom have they grown huge. Cases with associated ovarian masses are rare and frequently misdiagnosed. A 44 year old, postmenopausal female, presented with abdominal distension and pain. Radiology was suggestive of broad ligament fibroid with ovarian masses. On laparotomy she was found to have huge ovarian masses with a huge cervical fibroid. Bilateral mass excision done followed by cervical myomectomy followed by hysterectomy was done. Cervical fibroids may give rise to greater surgical difficulty by virtue of relative inaccessibility and close proximity to bladder and ureter. Occurrence of bilateral huge ovarian masses with a huge cervical fibroid is very rare. The management of such cases requires great surgical skill.